2017
DOI: 10.1007/s00421-017-3614-0
|View full text |Cite
|
Sign up to set email alerts
|

High intensity interval training does not impair strength gains in response to resistance training in premenopausal women

Abstract: In conclusion, performing HIIT on a cycle ergometer before resistance training does not seem to impair muscle strength increases in the knee extensors or elbow flexors of pre-menopausal women. This information should be considered when prescribing exercise sessions, since both activities may be combined without negative effects in muscle strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 60 publications
0
8
0
1
Order By: Relevance
“…36,39 None of the soft tissue laxity studies were graded down for indirectness, as little information exists on the impact of BMI on soft tissue laxity, and studies have reached contradictory conclusions on the impact of activity level on soft tissue laxity. 23,65,67,69 Muscle injury/strength studies were graded down if the outcome measured was not generalizable to the other muscle strength study outcomes or if participants had more than a low recreational activity level because training can influence muscle strength. 23,69 In the soft tissue injury section, studies that were downgraded in 1 area were scored as “serious,” and those that were downgraded in 2 areas were scored as “very serious.” In the muscle injury/strength section, to distinguish quality-of-evidence scores among this body of literature, studies downgraded in both areas were scored as “serious,” and no studies were scored as “very serious.”…”
Section: Methodsmentioning
confidence: 99%
“…36,39 None of the soft tissue laxity studies were graded down for indirectness, as little information exists on the impact of BMI on soft tissue laxity, and studies have reached contradictory conclusions on the impact of activity level on soft tissue laxity. 23,65,67,69 Muscle injury/strength studies were graded down if the outcome measured was not generalizable to the other muscle strength study outcomes or if participants had more than a low recreational activity level because training can influence muscle strength. 23,69 In the soft tissue injury section, studies that were downgraded in 1 area were scored as “serious,” and those that were downgraded in 2 areas were scored as “very serious.” In the muscle injury/strength section, to distinguish quality-of-evidence scores among this body of literature, studies downgraded in both areas were scored as “serious,” and no studies were scored as “very serious.”…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, females were assessed in the study by Aoki whereas we assessed only males. Previous studies have shown differences in muscle fatigability [6,8,19] and responsiveness to creatine supplementation between sexes [20,21].…”
Section: Discussionmentioning
confidence: 97%
“…Concurrent exercise (CE) involves the combination of aerobic exercise (AE) and resistance training in the same training session [1]. CE is common practice among exercising individuals and athletes and increases physical performance and body composition [2][3][4][5][6]. However, previous studies have shown that performing AE before resistance training results in acute decreases in muscle performance [2,4,[7][8][9][10], possibly due to an increase in peripheral fatigue, AMP-activated protein kinase (AMPK) and Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) signaling and decrease in satellite cell activity [1].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed no acute interference in the signaling of contractile proteins and mitochondrial biogenesis indicators, which suggests that this combination may favor the optimization of adaptation. However, in a recent randomized clinical trial, 14 the effects on strength indicators and cardiometabolic risk factors associated with 8 weeks of RT only and combined HIIT and RT in premenopausal women were evaluated. The authors concluded that HIIT before RT did not cause any interference effects on strength gains or induce significant changes in body composition or blood pressure.…”
Section: Introductionmentioning
confidence: 99%